Development and Validation of Self-Regulation Scale among Late Adolescents - , Ruchi Singh; , Suman Audichya (Archives of Current Research International, 2025)
Self-regulation is defined from an applied perspective as the act of managing cognition and emotion to enable goal-directed actions like organizing behavior, controlling impulses, and solving problems constructively necessary for success in college, relationships, and the workplace. The study’s aim was to construct and validate Self-Regulation Scale among late adolescents. The Self-Regulation Scale (SRS) consisted of 60 statement on selected dimensions of self-regulation. To establish the content validity, Self-Regulation Scale was evaluated by subject experts and thereafter reliability of the scale was calculated through pilot study. A total sample of 60 late adolescents i.e. 20 respondents from nuclear families, 20 respondents from single parent families and 20 respondents from joint families, between the ages of 19-21 years were selected through simple random sampling method from College of Community and Applied Sciences, MPUAT, Udaipur. For deriving reliability of the scale, split-half method was used. This finding of reliability and validity scores suggested that SRS is an acceptable instrument for assessment self-regulation of late adolescents.